Consumo de energia e crescimento econômico: uma relação em estudo com foco nos países componentes do BRICS - Mendes, Carlos Augusto Nogueira (2014)
The issue of energy consumption and its impact on economic growth is recurring today. Specifically in scenarios finiteness of energy sources, external price shocks of these inputs and the environmental agenda requiring replacement of the use of fossil fuels, this topic has found strong echo in the literature. Simultaneously, the existence of countries that have demonstrated strength for the growth of their economies, emerges as a privileged field of research which will put emphasis the relationship between energy consumption and economic growth. In reference countries are the members of the group denominated BRICS. Brazil, Russia, India, China and South Africa are the members of this group and are characterized by growth rates above the world average, in addition to having leading positions in inflows of foreign direct investment, surpassing Europe and the United States. To carry out this study, we used World Bank data on time series on GDP, Consumption, Gross Fixed Capital and Number of Patents Required, the last two being employed as control variables and serving as a proxy for Capital Stock and Technological Progress, respectively. Were used as empirical methods of analysis two regression models with autoregressive and variables with a lag, so as to better capture the influence of time on the variables. The Energy Consumption was used as one of the dependent variable in one of the models and GDP as use in the other model, for each of the countries. The results showed, with the exception of South Africa, that the influence of the consumption of energy is fundamental to the maintenance of Economic Growth in the remaining four BRICS countries, so any government action aimed at changing the energy supply should consider this feature.